DOENÇA DE HIRSCHSPRUNG: UM RELATO DE CASO - Conjeto Luiz Da Silva Neto; Mariana Machado Alves Andrade; Vitória Martins Braga; Bruna do Nascimento Pereira; Robson de Oliveira Brito; Marco Aurélio Pereira Gomes; Cintia Rodrigues de Sousa (UniEVANGÉLICA, 2018)
Objective: To report a case of Hirschsprung's disease in a 23-year-old patient, diagnosed at the Santa Casa de Misericórdia Hospital in Anápolis, Goiás. Case description: A 23-year-old female patient with a history of abdominal distension and intestinal constipation since birth, with the need to use oral laxatives for evacuation. Rectal biopsy revealed the absence of ganglion cells, in addition to hyperplasia of nervous fillets and discrete hypertrophy of the muscular layer itself of the rectal mucosa, confirming an ultra-short form of aganglionose. Conclusions: The importance of recognizing the signs and symptoms of this disease is evident, which allows the early diagnosis of Hirschsprung's disease in order to bring an improvement in the patient's quality of life.